KOMPARASI PENGGUNAAN ANALYSIS REGULATORY METHOD SEBAGAI INSTRUMEN PENDUKUNG KEBIJAKAN DALAM PENYUSUNAN PERATURAN PERUNDANG-UNDANGAN - Ihsanul Maarif, Ihsanul; Arifin, Firdaus (LITIGASI, 2022)
The promulgation of laws has been stipulated in Law Number 12 of 2011 concerning Guidelines for the Promulgation of Laws, which has been changed post enactment of Law Number 13 of 2022 on Second Amendment of  Law Number 12 of 2011, one of which is the application of the Regulatory Impact Analysis (RIA) and the Rule, Opportunity, Capacity, Communication, Interest, Process Method, and Ideology (ROCCIPI) as the basis for the Establishment of Legal Products in e Academic Manuscript of the Bill of Law/Regional Regulation.  Integrating the methods into Academic Manuscripts is incorrect considering that it serves as the justification (philosophical, sociological, and juridical) which is academic or scientific in nature upon the conclusion of Laws and Regional Regulations. (RIA) is an analysis method of policies that acts as a companion to academic manuscripts called the RIA Statement. This is interesting to study of how is the development of the RIA and ROCCIPI in promulgating laws? How do the techniques for preparing academic manuscripts pre and post the enactment of Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 compare? Keywords: Regulatory Impact Analysis; Rule, Opportunity, Capacity, Communication, Interest, Process, and Ideology; Legal Products.